Molecular MR imaging of fibrosis in a mouse model of pancreatic cancer - Polasek, Miloslav; Yang, Yan; Schühle, Daniel T; Yaseen, Mohammad A; Kim, Young R; Sung, Yu Sub; Guimaraes, Alexander R; Caravan, Peter (Scientific reports, 2017)
Fibrosis with excessive amounts of type I collagen is a hallmark of many solid tumours, and fibrosis is a promising target in cancer therapy, but tools for its non-invasive quantification are missing. Here we used magnetic resonance imaging with a gadolinium-based probe targeted to type I collagen (EP-3533) to image and quantify fibrosis in pancreatic ductal adenocarcinoma. An orthotopic syngeneic mouse model resulted in tumours with 2.3-fold higher collagen level compared to healthy pancreas. Animals were scanned at 4.7 T before, during and up to 60 min after i.v. injection of EP-3533, or of its non-binding isomer EP-3612. Ex-vivo quantification of gadolinium showed significantly higher uptake of EP-3533 compared to EP-3612 in tumours, but not in surrounding tissue (blood, muscle). Uptake of EP-3533 visualized in T1-weighted MRI correlated well with spatial distribution of collagen determined by second harmonic generation imaging. Differences in the tumour pharmacokinetic profiles of EP-3533 and EP-3612 were utilized to distinguish specific binding to tumour collagen from non-specific uptake. A model-free pharmacokinetic measurement based on area under the curve was identified as a robust imaging biomarker of fibrosis. Collagen-targeted molecular MRI with EP-3533 represents a new tool for non-invasive visualization and quantification of fibrosis in tumour tissue.
Keywords: Contrast Media; duktální karcinom slinivky břišní; zvířata; Cell Line, Tumor; Collagen; Biomarkers; biologické markery; nádorové buněčné linie; Magnetic Resonance Imaging; Molecular Imaging; myši; kontrastní látky; nádory slinivky břišní; magnetická rezonanční tomografie; Animals; gadolinium; Fibrosis; fibróza; Mice; Pancreatic Neoplasms; Disease Models, Animal; Gadolinium; Carcinoma, Pancreatic Ductal; kolagen; modely nemocí na zvířatech; molekulární zobrazování